Cloning of and complementation tests with alkaline phosphatase regulatory genes (phoS and phoT) of Escherichia coli. - Amemura, M (1982)
The regulatory genes of alkaline phosphatase, phoS and phoT, of Escherichia coli were cloned on pBR322, initially as an 11.8-kilobase EcoRI fragment. A restriction map of the hybrid plasmid was established. Deletion plasmids of various sizes were constructed in vitro, and the presence of phoS and phoT genes on the cloned DNA fragments was tested by introducing the plasmids into phoS64 and phoT9 strains for complementation tests. One set complemented only phoS64 but not phoT9; the other set complemented only phoT9 but not phoS64. We conclude that phoS64 and phoT9 mutations belong to different complementation groups and probably to different cistrons. The hybrid plasmid with the 11.8-kilobase chromosomal fragment also complemented the phoT35 mutation. A smaller derivative of the hybrid plasmid was constructed in vitro which complemented phoT35 but did not complement phoS64, phoT9, or pst-2. Our results agree with the suggestion that phoT35 lies in a different complementation group from phoS, phoT, or pst-2 (Zuckier and Torriani, J. Bacteriol. 145:1249--1256, 1981). Therefore, we propose to designate phoT35 as phoU. The effect of amplification of phoS or phoT on alkaline phosphatase production was examined. It was found that multiple copies of the phoS gene borne on pBR322 repressed enzyme production even in low-phosphate medium, whether it was introduced into wild-type strains (partially repressed) or phoR (phoR68 or phoR17) strains (fully repressed), whereas the introduction of multicopy plasmids bearing the phoT gene did not affect the inducibility of the enzyme.